Clinical Outcomes of Taiwanese Patients with cT4 Oral Cavity Squamous Cell Carcinoma: Toward the Identification of the Optimal Initial Treatment Approach for cT4b Patients - Liao, Chun-Ta; Wen, Yu-Wen; Lee, Shu Ru; Liu, Tsang-Wu; Tsai, Sen-Tien; Tsai, Ming-Hsui; Lin, Jin-Ching; Lou, Pei-Jen; Chu, Pen-Yuan; Leu, Yi-Shing; Tsai, Kuo-Yang; Terng, Shyuang-Der; et al. (Annals of surgical oncology, 2017)
Background The National Comprehensive Cancer Network guidelines recommend that patients with oral cavity squamous cell carcinoma (OSCC) and cT4b disease should be either included in clinical trials or treated with a nonsurgical approach. However, surgery may be feasible in selected patients with adequate safety margins. Using the nationwide Taiwanese Cancer Registry Database, we examined the prognosis of cT4b OSCC patients in relation to their treatment approach. Methods Of the 18,910 patients with previously untreated first primary OSCC identified between 2004 and 2010, 492 (2.6 %) had cT4b tumors. Of them, 327 (66 %) received initial treatment with surgery, whereas 165 (34 %) were initially treated with a nonsurgical approach. Of the latter group, 78 patients subsequently underwent surgery. A 5-year disease-specific survival (DSS) ≥45 % was considered as a favorable outcome. Results Better 5-year DSS and overall survival (OS) rates were observed in cT4b patients initially treated with surgery (vs. nonsurgery; DSS, 51 vs. 38 %; OS, 43 vs. 27 %, respectively, p < 0.001). Of the participants initially treated with surgery, patients with cN0–2 disease had better 5-year survival rates (DSS: cN0, 59 %; cN1, 53 %; cN2, 46 %; OS: cN0, 49 %; cN1, 50 %; cN2, 37 %) than those with cN3 disease (DSS: 0 %; OS: 0 %). Among cT4b patients who initially received a nonsurgical treatment, subjects who subsequently underwent surgery showed better outcomes. Conclusions Primary surgery is performed in approximately two-thirds of cT4b OSCC patients, with cN0–2 cases showing a good prognosis. Patients who initially received a nonsurgical approach can subsequently be treated with surgery and achieve favorable outcomes.